2013
DOI: 10.1007/s00181-013-0687-4
|View full text |Cite
|
Sign up to set email alerts
|

Preference-directed regulation when ethical environmental policy choices are formed with limited information

Abstract: Preference-directed regulation (PDR) can supplement traditional environmental policies through frequent regulatory revision (Livermore, 2007). Stakeholders can use PDR to garner popular support for a specific policy. By providing individuals with information that augments their opinions about the effectiveness of a policy at driving environmental outcomes, stakeholders can induce preference switching in favor of or in detriment to a specific policy. This paper documents the extent to which this is true using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In such contexts, government authorities and corporations are frequently unwilling to follow the praxis of negotiated conflict settlement, while some defenders and their movements refuse to back down on the premise that sustained contestation will further erode abuses of power, even if at the cost of deadly repression. The cases study literature suggests that likelihood of killings of environmental and land defenders thus seem particularly acute in middle-income countries with semi-authoritarian regimes, a recent history of armed conflicts and/or high homicides rates, and a high prevalence of conflicts around resource exploitation projects, as seen in Latin America (see Bebbington and Bury, 2013;Temper et al, 2015;Jeffords and Thompson, 2016;McNeish, 2018;Middeldorp and Le Billon, 2019). Butt et al (2019) have shown that weak rule of lawbased on the World Justice Project index -correlates with higher rates of environmental and land defender killings, echoing more general findings that the most significant variable increasing political killings besides civil war is a lack of judicial independence (Hill and Jones, 2014).…”
Section: What Are the Main Determinants Of Killings?mentioning
confidence: 99%
See 2 more Smart Citations
“…In such contexts, government authorities and corporations are frequently unwilling to follow the praxis of negotiated conflict settlement, while some defenders and their movements refuse to back down on the premise that sustained contestation will further erode abuses of power, even if at the cost of deadly repression. The cases study literature suggests that likelihood of killings of environmental and land defenders thus seem particularly acute in middle-income countries with semi-authoritarian regimes, a recent history of armed conflicts and/or high homicides rates, and a high prevalence of conflicts around resource exploitation projects, as seen in Latin America (see Bebbington and Bury, 2013;Temper et al, 2015;Jeffords and Thompson, 2016;McNeish, 2018;Middeldorp and Le Billon, 2019). Butt et al (2019) have shown that weak rule of lawbased on the World Justice Project index -correlates with higher rates of environmental and land defender killings, echoing more general findings that the most significant variable increasing political killings besides civil war is a lack of judicial independence (Hill and Jones, 2014).…”
Section: What Are the Main Determinants Of Killings?mentioning
confidence: 99%
“…Such high-level initiatives reflect a growing concern about the rise of anti-environmental movements and their backing not only by many conservative governments but also left-wing 'neo-extractivist' regimes (Rowell, 2017;Tilzey, 2019). 2 A growing body of scholarly literature is more systematically studying the persecution of environmental defenders to better understand risk factors (Clark, 2009;Jeffords and Thompson, 2016;Butt et al, 2019;Middeldorp and Le Billon, 2019;Scheidel et al, 2020). The case study literature suggests that killings of environmental and land defenders are particularly prominent in countries experiencing high levels of inequality and corruption, historical marginalization of Indigenous and peasant communities, a liberalization of foreign and private investment into landbased sectors, weak rule of law and recent reversals in partial democratization processes taking place within a broader context of high homicidal violence and impunity rates (Middeldorp and Le Billon, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation